Neotectonic basin and landscape evolution in the Eastern Cordillera of NW Argentina, Humahuaca Basin (~24°S) - Heiko, Pingel (2013)
The intermontane Quebrada de Humahuaca Basin (Humahuaca Basin) in the Eastern Cordillera of the southern Central Andes of NW Argentina (23°–24°S) records the evolution of a formerly contiguous foreland-basin setting to an intermontane depositional environment during the late stages of Cenozoic Andean mountain building. This basin has been and continues to be subject to shortening and surface uplift, which has resulted in the establishment of an orographic barrier for easterly sourced moisture-bearing winds along its eastern margin, followed by leeward aridification. We present new U–Pb zircon ages and palaeocurrent reconstructions suggesting that from at least 6 Ma until 4.2 Ma, the Humahuaca Basin was an integral part of a largely contiguous depositional system that became progressively decoupled from the foreland as deformation migrated eastward. The Humahuaca Basin experienced multiple cycles of severed hydrological conditions and subsequent re-captured drainage, fluvial connectivity with the foreland and sediment evacuation. Depositional and structural relationships among faults, regional unconformities and deformed landforms reveal a general pattern of intrabasin deformation that appears to be associated with different cycles of alluviation and basin excavation in which deformation is focused on basin-internal structures during or subsequent to phases of large-scale sediment removal.